EVALUASI PENERAPAN PRINSIP-PRINSIP DAN KRITERIA EKOWISATA DI KAWASAN TAMAN WISATA ALAM KAWAH IJEN BANYUWANGI - Sri Widowati; Nyoman Mastiani Nadra (Politeknik Negeri Bali, 2013)
The development of tourism was so fast at the last decade, but it was lacked attention for the environment, culture and the welfare of the society, so that the alternative tourism accurred as a new concept in the development of tourism.The concept was quite different from the concept of the conventional tourism. This new concept was very wellknown as a modern tourism that put the natural and the cultural conventional as the priority and to increase the economy of local society or the local people, and finally this concept is known as the term ”Ecotourism”. The result of the seminar at the National Ecotorism in Bali that was held on August 25 until August 26, 2006 produced 9 principles of the ecotourism which could give the recomendations in relation to the Sustainable Tourism. The evaluation result of the principles and criteria of ecotourism at the natural tourist object Ijen Creater in Taman Sari Village, Banyuwangi in some cases it had the similarities with the principles and criteria of the formulation of the seminar and the course of ecotourism in 2006, which was used as the reference to measure the standard of the ecoturism which was legalized nationally that refered to the Green Globe 21 agreed and trusted internationally.